ECOLOGY OF INFLUENZA VIRUS IN WILD BIRD POPULATIONS IN CENTRAL ASIA - V. Yu. Marchenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The study provides the results of AIV surveillance in Central Asia region during 2003-2009. We have analyzed. 2604 samples from wild birds. These samples were collected in Kazakhstan. (279), Mongolia (650), and Russia (1675). Isolated viruses from samples collected in Mongolia (13 isolates) and. in Russia (4 isolates) were described. Virological analysis has shown that 6 isolates belong to H3N6 subtype and. 5 isolates belong to H4N6 subtype. Two H1N1 influenza viruses, one H10N7 virus, two H3N8 viruses, and. H13N8 virus, which is new for Central Asia, have been also isolated. Samples were taken from birds of 6 orders, including several species, preferring water and semi-aquatic biotopes, one species, preferring dry plain regions, and one more species which can inhabit both dry and. water biotopes.